Preparing educators for the digital age: teacher perceptions of active teaching methods and digital integration - Abildinova, Gulmira; Abdykerimova, Elmira; Assainova, Almagul; Mukhtarkyzy, Kaussar; Abykenova, Dariya (Frontiers in Education, 2024)
IntroductionThis study investigates higher education teachers’ perceptions of active teaching methods—Case-Based Learning (CBL), Problem-Based Learning (PBL), and Team-Based Learning (TBL)—and their integration with digital technologies. These pedagogical strategies are crucial for fostering critical thinking, collaboration, and problem-solving skills among students, especially in the digital age. Despite their benefits, challenges such as resource limitations, time constraints, and insufficient training hinder their implementation.MethodsA mixed-methods approach was adopted, involving 104 educators from various higher education institutions in Kazakhstan. Participants underwent an eight-week training program consisting of 72 h of workshops, collaborative activities, and self-paced learning. Pre- and post-training assessments measured knowledge, confidence, and practical application of active teaching methods. Surveys, feedback sessions, and peer evaluations provided qualitative and quantitative insights into participants’ experiences and challenges.ResultsThe training program significantly improved participants’ knowledge, confidence, and ability to implement CBL, PBL, and TBL. Post-training assessments showed a 4.2-point increase in confidence and practical application scores. Most educators (66.35%) reported moderate adaptability of these methods to their current educational programs, while 27.88% achieved high adaptability. Participants identified resource limitations (43.27%) and time constraints (33.65%) as key challenges. Problem-Based Learning (PBL) was preferred for fostering critical thinking and problem-solving, with a majority (51.92%) favoring it over other methods. Digital technologies, such as Moodle and augmented reality tools, enhanced teaching effectiveness and student engagement.DiscussionThe findings highlight the transformative potential of active teaching methods and digital integration in higher education. Educators across various academic positions and institutions perceived these methods as highly effective, aligning with the Diffusion of Innovations Theory. Challenges such as insufficient resources and curriculum misalignment were significant barriers to broader adoption. Continuous professional development, institutional support, and strategic resource allocation are crucial for optimizing these methods’ impact.